(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
From time immemorial India is considered to be a land ofminorities comprising various groups — racial religious, linguistic andcultural Hindus, Muslims, Buddhists, Christians, Sikhs, Jain, Jews and Parsishave been in this land for centuries. There was communal harmony and mutualunderstanding and, hence, in the ancient days, India witnessed run majorpolitical problems of the existence of minorities.